Cfdp1 controls the cell cycle and neural differentiation in the zebrafish cerebellum and retina. Issue 11 (24th May 2021) - Itoh, Tsubasa; Inoue, Shinsuke; Sun, Xiaoding; Kusuda, Ryo; Hibi, Masahiko; Shimizu, Takashi
Abstract: Background: Although the cell cycle and cell differentiation should be coordinately regulated to generate a variety of neurons in the brain, the molecules that are involved in this coordination still remain largely unknown. In this study, we analyzed the roles of a nuclear protein Cfdp1, which is thought to be involved in chromatin remodeling, in zebrafish neurogenesis. Results: Zebrafish cfdp1 mutants maintained the progenitors of granule cells (GCs) in the cerebellum, but showed defects in their differentiation to GCs. cfdp1 mutants showed an increase in phospho‐histone 3 (pH 3)‐positive cells and apoptotic cells, as well as a delayed cell cycle transition from the G2 to the M phase in the cerebellum. The inhibition of tp53 prevented apoptosis but not GC differentiation in the cfdp1 mutant cerebellum. A similar increase in apoptotic cells and pH 3‐positive cells, and defective cell differentiation, were observed in the cfdp1 mutant retina. Although mitotic spindles formed, mitosis was blocked before anaphase in both the cerebellum and retina of cfdp1 mutant larvae. Furthermore, expression of the G2/mitotic‐specific cyclin B1 gene increased in the cfdp1 mutant cerebellum. Conclusions: Our findings suggest that Cfdp1 regulates the cell cycle of neural progenitors, thereby promoting neural differentiation in the brain. Key Findings: Zebrafish mutants for a chromatin remodeling factor Cfdp1 showed defects in neuronal differentiation from neural progenitors in the cerebellum and retina. cfdp1 mutants showed an increase in phospho‐histone 3‐positive cells and apoptotic cells, as well as a delayed cell cycle transition in the cerebellum and retina. cfdp1 mutants displayed mitotic arrest and increased expression of the G2/mitotic‐specific cyclin B1 gene. Thus, Cfdp1 regulates the cell cycle of neural progenitors, thereby promoting neural differentiation in the brain.